Analisis finansial dan ekonomi usaha karamba jaring apung ikan kerapu tikus di Sulawesi Tenggara - ABDI, ABDI ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Objectives of the study are: 1) to know the influencing factors of production at floating net cage (FNC) business of polka dot grouper; 2) to know the used of efficiency of production factors at FNC business of polka dot grouper; 3) to know the influencing factors to production efficiency at FNC business of polka dot grouper; and 4) to know the cost and benefit at FNC business of polka dot grouper, from economic and financial aspect considering social aspect. The study carried out in Southeast Sulawesi with the sample amount 34 fisher farmers FNC of polka dot grouper, determination of sample using census method. Data analysis used the double logarithm regression, maximum likelihood estimation and cost benefit analysis in economic and financial with the social approach. The result of the study indicates that production FNC business of polka dot grouper influenced by amount the seed, fish food, permanent labor, non permanent labor and technical efficiency rating (management) of FNC business of polka dot grouper. Management factor represent the very determining factor increasing production because relating to ability and fisher farmer skill in managing FNC business of polka dot grouper. The used production factors of seed, fish food, permanent labor and non permanent labor at FNC business of polka dot grouper not yet efficient either through technical, allocative and economic. The family members, education and experience of fish breeding give the positive effect to production efficiency the FNC business of polka dot grouper. Increasing of fisher farmer age give the negative effect to production efficiency the FNC business of polka dot grouper. Increasing of seed size and time enlargement can improve the production efficiency at FNC business of polka dot grouper. Increasing of cage size, amount the enlargement box and fisher farmer house distance with breeding location will descend the production efficiency at FNC business of polka dot grouper. By economic and financial with the social cost and benefit approach, all patterns is FNC business of polka dot grouper feasible to business and developed. FNC business of polka dot grouper at size 8 m x 8 m, 4 enlargement boxes represent the best choice alternative to be developed because of it giving economic and financial benefit more large compared the FNC business of polka dot grouper the other size.